IMPROVING THE STUDENTS’ WRITING SKILL BY USING PROCESS WRITING APPROACH AT THE SECOND GRADE STUDENTS OF SMK GRAFIKA GOWA MAKASSAR - St Asriati; Maharida Maharida (Universitas Muhammadiyah Makassar, 2013)
The research questions of this research were how is the improvement of students’ skill in writing descriptive text views from its grammar through writing process approach at the second grade (TKJ Department) of SMK Grafika Pallangga, how is the improvement of students’ skill in writing descriptive text views from its organization through writing process approach at the second grade (TKJ Department) students of SMK Grafika Pallangga, and how is the activeness of students in writing descriptive text through writing process approach at the second grade (TKJ Department) students of SMK Grafika Pallangga. The researcher used Classroom Action Research (CAR). The aimed of this research were to find out the improvement of students’ writing skill and their activeness in the learning process through Writing Process Approach.Two cycles had been conducted, where each cycle consisted of four meetings. It employed writing test as the instrument. A number of subjects of the research were 42 students in the second grade (TKJ Department) conducted of 19 women and 23 men. The researcher took real data from the school to know the students’ writing skill. The results of the student's writing test in cycle 1 and cycle 2 had increased in different scores. There was increasing by students at the end action of the second cycle. The research findings indicated that use of writing process approach could increase the students’ writing skill. The means scores of students in Diagnostic test was 59.84 became 66.38 in cycle 1, and after revision in the cycle 2 the mean score in cycle 2 was 70.79 by implemented of descriptive text. The successful of minimal criteria (KKM) was 65 while cycle 1, there were 2 (4.76%) students get poor, 27 (64.29%) get fair, and 13 (30.95%) get good meant that students who achieved the successful minimal criteria (KKM) more than a half of them. In cycle 2 there was 25 (59.52%) get fair and 17 (40.48%) get fair.Keywords: Writing approach, students, and descriptive.